2000
DOI: 10.1046/j.1432-1327.2000.01687.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of porin isoforms expressed in tumor cells

Abstract: Mitochondria from malignant tumor cell lines show a higher capability for hexokinase binding than those from normal liver. To explore possible differences in hexokinase binding sites of mitochondria between tumor cells and normal liver, we characterized porin isoforms expressed in tumor cells. Cloning experiments on the three porin isoforms, VDAC1, VDAC2 and VDAC3 from malignant tumor cell line AH130 clearly showed that their primary structures were completely identical to those of the corresponding VDACs of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 31 publications
(47 reference statements)
3
56
0
2
Order By: Relevance
“…Alternatively, VDAC1 may represent the predominant form expressed in the tissues tested (41). On the other hand, both VDAC1 and VDAC2 are ubiquitously expressed, while VDAC3 has a more restricted organ distribution (42)(43)(44). VDAC isoforms appear to display different physiological functions (45), each isoform exhibiting different permeability properties (46), and binding of hexokinase, a protein that has also been proposed to be associated to the PTP (47, 48), appears to be a specific feature of VDAC1 (28).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, VDAC1 may represent the predominant form expressed in the tissues tested (41). On the other hand, both VDAC1 and VDAC2 are ubiquitously expressed, while VDAC3 has a more restricted organ distribution (42)(43)(44). VDAC isoforms appear to display different physiological functions (45), each isoform exhibiting different permeability properties (46), and binding of hexokinase, a protein that has also been proposed to be associated to the PTP (47, 48), appears to be a specific feature of VDAC1 (28).…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced expression of VDAC on tumor mitochondria in comparison to normal tissue has also been observed (Shinohara et al, 2000). Although several isoforms of VDAC are known, they do have similar kinetic characteristics, which indicate that the contribution of VDAC to enhanced HK binding and glucose phosphorylation is due to quantitative differences in binding site availability (Shinohara et al, 2000).…”
Section: The Voltage-dependent Anion Channelmentioning
confidence: 99%
“…Although several isoforms of VDAC are known, they do have similar kinetic characteristics, which indicate that the contribution of VDAC to enhanced HK binding and glucose phosphorylation is due to quantitative differences in binding site availability (Shinohara et al, 2000). The predominant form of VDAC expressed on mitochondria and known to interact with HK is VDAC-1.…”
Section: The Voltage-dependent Anion Channelmentioning
confidence: 99%
“…The molecular mechanism of HK-mediated protection against cell death involves HK-I and HK-II binding to the outer mitochondrial membrane protein, the voltage-dependent anion channel (VDAC) (8,9,(13)(14)(15)(16). Indeed, VDAC was shown to be up-regulated in cancer cells exhibiting elevated binding to HK-I and/or HK-II (17). Also, it has been recently shown that acute viruses, such as HEV, can protect infected cells from apoptotic death via enhanced VDAC and HK expression (18).…”
mentioning
confidence: 99%